Functional and logic programming : 14th International Symposium, FLOPS 2018, Nagoya, Japan, May 9-11, 2018, Proceedings /: 14th International Symposium, FLOPS 2018, Nagoya, Japan, May 9-11, 2018, Proceedings. (2018) - Unknown
No abstract available